2019
DOI: 10.1001/jamanetworkopen.2019.10005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Parental Incarceration With Psychiatric and Functional Outcomes of Young Adults

Abstract: Key Points Question Is parental incarceration associated with increased odds of offspring receiving psychiatric diagnoses during young adulthood and experiencing obstacles that can derail a successful transition to adulthood (eg, in health, legal, financial, and social domains)? Findings This cohort study, using data from a community-representative, longitudinal study, found that parental incarceration was associated with young adults’ increased odds of hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…15 These compounded disadvantages place children at high psychiatric, legal, social, and financial risk, including being at an amplified risk for future imprisonment. [14][15] Most states in the USA have modestly downsized their prisons since reaching their peak population levels, but the number of people incarcerated in the USA remains several times higher (670 people per 100 000 residents) than that of other highincome countries (eg, 94 per 100 000 in Germany and 45 per 100 000 in Japan). 7, [10][11] Inequities in the US criminal justice system stem from enduring the systemic effect of racial oppression, police force militarisation and assignment overreach, police brutality, and a large and dysfunctional community supervision structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 These compounded disadvantages place children at high psychiatric, legal, social, and financial risk, including being at an amplified risk for future imprisonment. [14][15] Most states in the USA have modestly downsized their prisons since reaching their peak population levels, but the number of people incarcerated in the USA remains several times higher (670 people per 100 000 residents) than that of other highincome countries (eg, 94 per 100 000 in Germany and 45 per 100 000 in Japan). 7, [10][11] Inequities in the US criminal justice system stem from enduring the systemic effect of racial oppression, police force militarisation and assignment overreach, police brutality, and a large and dysfunctional community supervision structure.…”
Section: Introductionmentioning
confidence: 99%
“…12 , 13 Mass incarceration has led to more than 2 million children in the USA having a parent incarcerated. 3 , 14 , 15 Many of these children live in low-income neighbourhoods, have lost siblings to violence, and experience food and housing insecurity. 15 These compounded disadvantages place children at high psychiatric, legal, social, and financial risk, including being at an amplified risk for future imprisonment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even with a reduction in overall incarceration rates for men, there has been a steady increase of incarcerated women (Carson, 2018), and the rate of incarcerated mothers has doubled since 1991 (up by 131%; Glaze & Maruschak, 2008). There are notable long-term impacts of having a parent incarcerated as a child that can be seen into adulthood, including greater risk of psychopathology, internalizing and externalizing traits, illegal drug use, having a criminal conviction, and becoming incarcerated (Gifford et al, 2019). However, there is a scarcity of research aiming to understand the long-term correlates of parental incarceration among second-generation female offenders.…”
mentioning
confidence: 99%
“…Additionally, the children living with family members or other guardians are reluctant to discuss why the parent was arrested and incarcerated (Mumola, 2004). Gifford et al (2019) found that parents incarcerated produced long-term psychological effects on their children. Their seven-year cohort study of 1,420 children and young adults found increased propensity of anxiety disorders, felony charges, time in jail, dropping out of high school, having a child before turning 18, and becoming more socially isolated compared with their peers who did not have a parent in prison.…”
Section: Reuniting Ex-inmates With Children: a Disconnectionmentioning
confidence: 99%